The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1017/cjn.2023.10
|View full text |Cite
|
Sign up to set email alerts
|

The Known Biology of Neuropathic Pain and Its Relevance to Pain Management

Abstract: Patients with neuropathic pain are heterogeneous in pathophysiology, etiology, and clinical presentation. Signs and symptoms are determined by the nature of the injury and factors such as genetics, sex, prior injury, age, culture, and environment. Basic science has provided general information about pain etiology by studying the consequences of peripheral injury in rodent models. This is associated with the release of inflammatory cytokines, chemokines, and growth factors that sensitize sensory nerve endings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 148 publications
(286 reference statements)
1
8
0
Order By: Relevance
“…This latter finding could be due to the innervation of upper cervical regions of the spinal cord by cranial muscles and dura or because of functional and anatomical similarities between spinal and medullary dorsal horns. Nevertheless, differences in the neuron subtypes that show strong associations for each type of pain reported is consistent with studies showing that chronic pain mechanisms and circuits differ by the nature of the injury 34,68,69 . It also fits that the number of neuron subtypes we identified as being highly enriched in open chromatin SNPs from patients with head/neck and multisite pain, which are likely to be combinations of inflammatory and neuropathic etiologies, was much greater than for the other types of pain.…”
Section: Discussionsupporting
confidence: 87%
“…This latter finding could be due to the innervation of upper cervical regions of the spinal cord by cranial muscles and dura or because of functional and anatomical similarities between spinal and medullary dorsal horns. Nevertheless, differences in the neuron subtypes that show strong associations for each type of pain reported is consistent with studies showing that chronic pain mechanisms and circuits differ by the nature of the injury 34,68,69 . It also fits that the number of neuron subtypes we identified as being highly enriched in open chromatin SNPs from patients with head/neck and multisite pain, which are likely to be combinations of inflammatory and neuropathic etiologies, was much greater than for the other types of pain.…”
Section: Discussionsupporting
confidence: 87%
“…The overall response of neuronal tissue to inflammatory mediators is described as “neuroinflammation” ( 167 170 ). It is characterized by glial cell proliferation and modulation of their phenotype as well as increased neuronal activity.…”
Section: Neuroinflammation and The Actions Of Primary Mediators On Pr...mentioning
confidence: 99%
“…At the pre-synaptic level, IL-1β enhances glutamatergic synaptic activities at the first synapses between the primary nociceptive afferents and dorsal horn neurons in the spinal dorsal horn by promoting glutamate release from presynaptic terminals 2 . IL-1β facilitates presynaptic glutamate release by enhancing presynaptic NMDA receptor activity [ 2 , 102 ]. At the postsynaptic level, IL-1β augments post-synaptic AMPA and NMDA receptor activities [ 4 , 62 , 103 ].…”
Section: Mechanisms Used By Glia To Cause Aberrant Neuronal Activity ...mentioning
confidence: 99%
“…The development of novel analgesics with higher potency and safer features is an unmet need. Studies over the past three decades have shown that, under neuropathic conditions, pathologic glial cells play a critical role in aberrant neuronal activity in both the peripheral nerve and the spinal dorsal horn, termed peripheral and spinal central sensitizations, respectively [ 2 ]. Glial cells orchestrate neuronal activities in the peripheral and central nervous systems by releasing proinflammatory mediators (cytokines, chemokines, and others) [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation